Development of Proteocephalus torulosus in the intermediate host under experimental conditions - Scholz, T (Journal of helminthology, 1993)
The development of the tapeworm Proteocephalus torulosus (Batsch, 1786) (Cestoda: Proteocephalidae), a parasite of cyprinid fish, was studied in the intermediate host under experimental conditions. The eggs of P. torulosus were typified by a relatively small outer envelope (hyaline membrane) and a thick middle layer surrounding the oncosphere. Incubation of P. torulosus eggs at different temperatures revealed the ability of some oncospheres to survive and remain infective to the intermediate host for up to 5 weeks at 5-7 degrees C, 12 days at 10-12 degrees C, and 8 days at 20-22 degrees C. Of 8 copepod species used in these experiments, complete development of larvae was observed only in Cyclops strenuus. Growth was completed in 9-12 days at 20-22 degrees C and four weeks at 9-10 degrees C. During development the cercomer was not observed. The infectivity of larvae from C. strenuus for the definitive hosts, cyprinid fish, was very low and only one chub of 26 fish used for feeding experiments (21 chub, Leuciscus cephalus, 3 bleak, Alburnoides bipunctatus, 1 rudd, Scardinius erythrophthalmus--all the family Cyprinidae, and 1 loach, Noemacheilus barbatulus--the family Cobitidae) became infected.
Keywords: teplota; korýši; Cestoda; nemoci ryb; Water; Animals; Fish Diseases; Cestode Infections; Temperature; zvířata; cestodózy; voda; Crustacea; Cyprinidae